SISTEM INFORMASI EKSEKUTIF STOK DAGING SAPI DI PULAU JAWA - Brastama Putra, Agung; Cita Gemilang, Canang; Bintang Fajar, Mohammad; Mustofa.K.Pasya, Ahmad (ReTII, 2019)
The need for a system that can visualize data to support the decision making process is increasingly needed. This paper produces applications that can visualize data with an executive information system approach related to beef stock in Java with drilldown features and what-if analysis. The methodology we use is the SIE approach with graphs that can do drilldown and what-if analysis programs regarding cattle population calculations based on beef stock data.